Tanggung Jawab Negara Peluncur Terhadap Sampah Ruang Angkasa Menurut Hukum Lingkungan Internasional - Mhd Nasir Sitompul (Iuris Studia: Jurnal Kajian Hukum, 2021)
The development of technology in the use of space resources at this time is very fast. The state has the right to launch a satellite as a national program that has sovereignty so that it can become the main subject of international law. The profits obtained in the use of space are indeed a positive and profitable activity. As a result of these activities, it also has a negative impact from the results of the use of space which causes waste that is still orbiting in space. This is a concern for countries because it turns out that pollution does not only exist on earth but also in space which can disrupt the space environment. This study was conducted to examine the law for countries that launch celestial bodies that result in space waste by using normative juridical research with descriptive analysis sourced from secondary data by processing data from primary legal materials, secondary legal materials, and legal materials. tertiary. The purpose of this study is to determine the responsibility of the launching state in the management of space waste. This study provides an analysis that international law has implemented provisions for countries that launch celestial bodies into space freely without discrimination and with peaceful purposes. International environmental law has not explicitly regulated space waste, where international environmental law instruments provide stipulations that each country must preserve the environment in utilizing natural resources based on sustainable development. The launching state has the responsibility (responsibility) for the launch of the celestial body in the form of prevention before the impact of space debris with the management of space waste management